2016
DOI: 10.1093/mnras/stw1339
|View full text |Cite
|
Sign up to set email alerts
|

Recent X-ray observations of the symbiotic star AG Peg: do they signify colliding stellar winds?

Abstract: We present an analysis of recent X-ray observations of the symbiotic star AG Peg. The X-ray emission of AG Peg as observed with Swift in 2015 shows considerable variability on time scale of days as variability on shorter time scales might be present as well. Analysis of the X-ray spectra obtained in 2013 and 2015 confirms that AG Peg is an X-ray source of class β of the X-ray sources amongst the symbiotic stars. The X-ray emission of AG Peg as observed with ROSAT (1993 June) might well originate from colliding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Finally, it is worth noting that the X-ray emission of AG Peg in 2017 returned to its level before the outburst of this object in 2015. The 2017 observed flux in the 0.3 -3 keV energy range of 6.21 × 10 −13 ergs cm −2 s −1 is about a factor of 2 lower than the average flux in 2015 and comparable to the value of the pre-outburst observations in 2013 (see table 1 Zhekov & Tomov 2016).…”
Section: Global Spectral Modelssupporting
confidence: 59%
See 3 more Smart Citations
“…Finally, it is worth noting that the X-ray emission of AG Peg in 2017 returned to its level before the outburst of this object in 2015. The 2017 observed flux in the 0.3 -3 keV energy range of 6.21 × 10 −13 ergs cm −2 s −1 is about a factor of 2 lower than the average flux in 2015 and comparable to the value of the pre-outburst observations in 2013 (see table 1 Zhekov & Tomov 2016).…”
Section: Global Spectral Modelssupporting
confidence: 59%
“…We note that the ROSAT spectrum considered in this study is the same one as in Zhekov & Tomov (2016): its data reduction and spectral extraction are described in section 2 therein. It is worth recalling that the ROSAT spectrum is not of that high quality as the EPIC spectra are: it has only ∼ 400 source counts (to compare with ∼ 5000 source counts in the pn and MOS spectra; see Section.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors ascribed the origin of the strong and variable X-rays to shocks in the variable ejecta. Analysing the same Swift/XRT observations, Zhekov & Tomov (2016) came to the conclusion that the characteristics of the X-ray emission from the 2015 outburst could not result from colliding stellar winds in a binary system as was indicated by previous ROSAT observations from June of 1993. Using optical spectroscopy and BV photometry, Tomov et al (2016) concluded that the 2015 outburst of AG Peg places it among the classical Z And-type symbiotic binary systems.…”
Section: Introductionmentioning
confidence: 58%